2007
DOI: 10.1149/1.2748637
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Cyclability of an Aqueous Lithium-Ion Battery LiNi[sub 1∕3]Mn[sub 1∕3]Co[sub 1∕3]O[sub 2]∕Li[sub x]V[sub 2]O[sub 5] by Polyaniline Coating on the Anode

Abstract: The reasons for capacity fading of an LiNi 1/3 Mn 1/3 Co 1/3 O 2 /5 M LiNO 3 ͑pH 11͒/Li x V 2 O 5 lithium-ion cell based on structure and dissolution of transition metals were investigated. X-ray diffraction and inductively coupled plasma results showed that the properties of the anode have an impact on the cycle life of the cell. To stabilize the cycling capacity of the anode, and thus improve the cycle life of the cell, coating with a conductive polyaniline on the surface of the anode was proposed. Cycle tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 19 publications
2
28
1
Order By: Relevance
“…The discharge capacity is found to be around 70 mAh g −1 , which is better than that at the pristine LiNi 1/3 Mn 1/3 Co 1/3 O 2 . Such an enhancement in the capacity (about 10 mAh g −1 ) is reported in literature upon coating polypyrrole [20] and polyaniline [21] for Li x V 2 O 5 anode material; 15 and 20 wt.% PPy added composite electrodes delivered an initial capacity of 59 and 54 mAh g −1 , respectively, which are less than that of pristine LiNi 1/3 Mn 1/3 Co 1/3 O 2 . The decrease in the capacity of 15 and 20 wt.% PPy added composite electrodes can be explained as follows.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The discharge capacity is found to be around 70 mAh g −1 , which is better than that at the pristine LiNi 1/3 Mn 1/3 Co 1/3 O 2 . Such an enhancement in the capacity (about 10 mAh g −1 ) is reported in literature upon coating polypyrrole [20] and polyaniline [21] for Li x V 2 O 5 anode material; 15 and 20 wt.% PPy added composite electrodes delivered an initial capacity of 59 and 54 mAh g −1 , respectively, which are less than that of pristine LiNi 1/3 Mn 1/3 Co 1/3 O 2 . The decrease in the capacity of 15 and 20 wt.% PPy added composite electrodes can be explained as follows.…”
Section: Resultssupporting
confidence: 64%
“…Electronically conducting polymers such as polypyrrole, polyaniline, and polythiophene have been used to form composite cathode materials such as LiMn 2 O 4 -PPy [20] and V 2 O 5 -PAni [21] to improve the conductivity, coulombic efficiency, rate capability, and stabilize the cycle capacity of the electrode material. In case of LiMn 2 O 4 -PPy composite, the addition of polypyrrole increases the capacity of the pure LiMn 2 O 4 from 110 to 125 mAh g −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al. 39 confirmed that the crystalline structure of Li x V 2 O 5 became nearly amorphous after 40 cycles in ARLB. The formation of new compounds was also considered to be the cause for capacity fading of TiP 2 O 7 by Chen and his group25.…”
Section: Discussionmentioning
confidence: 90%
“…Even so, the good capacity retention observed at high rates cannot offset the very low capacity delivered by the cell under these conditions. Actions aimed at reducing or avoiding dissolution of the active material in the electrolyte, such as those proposed by Wang et al [20], who coat particle surfaces with water-resistant agents, might provide an effective solution.…”
Section: Resultsmentioning
confidence: 99%